Extremely High-Efficiency Coupling Method for Hollow-Core Photonic Crystal Fiber - Danyun Fan; Zhiqiang Jin; Guanghui Wang; Fei Xu; Yanqing Lu; Dora Juan Juan Hu; Lei Wei; Ping Shum; Xuping Zhang (IEEE Photonics Journal)
We report a novel low-loss splicing approach for hollow-core photonic crystal fiber (HC-PCF) and conventional single mode fiber (SMF) by inserting an etched SMF tip into the hollow core. If the divergence solid angle (DSA) of the inserted fiber tip is smaller than the guiding solid angle (GSA) of HC-PCF, all the radiated optical power from the tip will be collected by PCF with an extremely high coupling efficiency and guided by the PCF based on photonic bandgap effect. A DSA-GSA matching model is proposed to calculate the efficiency for different splicing situations. In the optimal condition of GSA > DSA, the transmission loss could approach zero, only including the scattering loss of etched fiber. Then, we experimentally demonstrate the splicing between NKT HC19-1550-01 and SMF-28 with coupling efficiency of 84.5%, agreeing well with the theoretical result of 85%. In addition, our proposed method is coaxiality error free, angle deviation free, and insertion length insensitive. This new technique is expected to provide new possibilities in some special system designs for HC-PCF-based applications.